Perlindungan Hukum Terhadap Konsumen Melalui Kewajiban Pendaftaran Jaminan Fidusia - Emir Adzan Syazali (Universitas Adiwangsa Jambi, 2021)
ABSTRACT The provision of credit by finance companies is currently in great demand by the public as a means to make it easier to own an object by making payments in installments every month. The process of granting credit by finance companies requires a guarantee for the object. The problem is the form of fiduciary legal registration protection for consumers and what benefits are obtained from consumers, normative juridical methods based on legal literature literature results In consumer financing agreements legal protection for creditors in a fiduciary guarantee agreement is born on the imposition of fiduciary guarantees made notarized, and continues to be emphasized with the registration of these agreements, the Fiduciary Guarantee Act has attempted to provide a technical protection for the interests of creditors, but unfortunately this system is not approved by concretely confirming the legal protection for creditors in a Fiduciary agreement, among others, caused either by regulations that provide a position weak for creditors, such as the absence of firmness in execution regarding execution, even though the object of fiduciary security concerns moving objects which are locked very quickly so that they are prone to embezzlement